Of eyes, glasses, and mirrors (Journal of Parents and Teachers, 2025)
The truth is that life is fascinating, and we must look at it through the right glasses in order to live it the right way. Those glasses will project to our eyes what is necessary to learn from each and every thing that happens to us. Therefore, throughout the article, we will find sections about glasses, the lens through which we look, or even the mirror.
Keywords: life; glasses; way; lens